Detection of BRCA1/2 pathogenic variants in patients with breast and/or ovarian cancer and their families. Analysis of 3,458 cases from Lower Silesia (Poland) according to the diagnostic algorithm of the National Cancer Control Programme - Doraczynska-Kowalik, Anna; Michalowska, Dagmara; Matkowski, Rafal; Czykalko, Ewelina; Blomka, Dorota; Semeniuk, Mariola; Abrahamowska, Mariola; Janus-Szymanska, Gabriela; Mlynarczykowska, Paulina; Szynglarewicz, Bartlomiej; Pawlak, Ireneusz; Maciejczyk, Adam; et al. (Frontiers in Genetics, 2022)
Breast and ovarian cancers are among the most common malignancies in the female population, with approximately 5-10% of cases being hereditary. BRCA1 and BRCA2 with other homologous recombination genes are the most tested genes in hereditary breast and ovarian cancer (HBOC) patients. As next-generation sequencing (NGS) has become a standard and popular technique, including for HBOC, it has greatly simplified and accelerated molecular diagnosis of cancer. The study group included 3458 HBOC patients or their relatives from Lower Silesia (Poland) (Voivodeship located in south-west Poland inhabited by 2.9 million people). All patients were tested according to the recommendations from the National Cancer Control Programme of the Ministry of Health for the years 2018-21. We tested 3400 patients for recurrent pathogenic variants for the Polish population: 5 BRCA1 founder variants (c.5266dup, c.181T>G, c.4035del, c.3700_3704del and c.68_69del), 2 PALB2 variants (c.509_510del, c.172_175del) and 3 CHEK2 variants (c.1100del, c.444+1G>A, g.27417113-27422508del (del5395). Next 260 patients from the study group were chosen for the BRCA1/2 NGS panel, and additionally selected marker pathogenic variants were tested using Sanger sequencing and MLPA methods in 45 and 13 individuals respectively. The analysis of BRCA1/2 in 3458 patients with HBOC or their relatives revealed 144 carriers of 38 different pathogenic variants (23 in BRCA1 and 15 in BRCA2). Among all detected variants 71.5% constituted founder pathogenic BRCA1 variants. Our study revealed that for the Lower Silesian population the first-line BRCA1/2 molecular test may be limited to only 3 variants in BRCA1 – c.5266dup, c.181T>G and c.4035del – but the aim should be to provide a full screening test of HBOC critical genes. The key and still growing role of molecular diagnostics of neoplasms, including HBOC, is undeniable. Therefore it is necessary to provide complete and optimal therapeutic and prophylactic algorithms in line with current medical knowledge.